Mediation in the Reflection of Law and Society European Perspectives - Holá, Lenka (Global trends in dispute resolution ;, 2022)
"Despite slow progress in use, mediation continues to consolidate its presence in dispute resolution. This important book argues that a more favourable socio-legal climate must be created for mediation to thrive, and accordingly analyses the legal, cultural, social, systemic and spatial aspects of the use of mediation in the legal practice of the different countries of the European Union (EU). Based on a spatiotemporal analysis and models of mediation in the EU, it pinpoints the social and cultural reasons for the fragmentation of its legal regulation and shows what paths are available to promote the effective implementation of mediation in social practice. It is the first book to capture the socio-legal context of mediation. A spatiotemporal analysis of the extent of use of mediation in a region as large and at the same time as diverse as the EU has never been carried out before. Using various methodological and conceptual approaches to analyse the legal and social aspects of introducing mediation to legal systems, the authors - all with long-term experience in the exercise and research of mediation directly in the field - provide invaluable insights into such facets of the use of mediation as the following: the social context that raises the need for mediation; obstacles to the wider use of mediation in resolving disputes between parties; the effects of social influences reflected in legislation that shape the laws of each country; the basic models that make up the system of access to mediation in specific EU Member States; the role of law as a tool for social change and its reflection in the legal regulation of mediation; and perspectives for further development of mediation in the EU. The legislative efforts proposed to enhance the regulation of mediation in EU countries are based on modern knowledge of law, sociology and psychology. As a unique combination of exploration of the theoretical determinants of mediation and an empirical study of the extent of its use in the European area, this book's fundamental contribution to the legal theory and practice of mediation is inarguable. Its analysis of mediation from three perspectives - as a means of improving citizens'access to justice, as a means of applying social justice in society, and as a means of restorative justice - are of the utmost value in today's global society. For users of mediation, EU institutions involved in mediation, EU Member State authorities addressing the issue of mediation, and the wider dispute resolution community worldwide, the book will be welcomed for the giant steps it takes toward refining arguments for the promotion of mediation and its development, in theory, research and practice"--